Chromosomal‐level genomes of three rice planthoppers provide new insights into sex chromosome evolution. (18th November 2020) - Ma, Weihua; Xu, Le; Hua, Hongxia; Chen, Mengyao; Guo, Mengjian; He, Kang; Zhao, Jing; Li, Fei
Abstract: The brown planthopper Nilaparvata lugens, white‐backed planthopper Sogatella furcifera, and small brown planthopper Laodelphax striatellus are three major insect pests of rice. They are genetically close; however, they differ in several ecological traits such as host range, migration capacity, and in their sex chromosomes. Though the draft genome of these three planthoppers have been previously released, the quality of genome assemblies need to be improved. The absence of chromosome‐level genome resources has hindered in‐depth research of these three species. Here, we performed a de novo genome assembly for N. lugens to increase its genome assembly quality with PacBio and Illumina platforms, increasing the contig N50 to 589.46 Kb. Then, with the new N. lugens genome and previously reported S. furcifera and L. striatellus genome assemblies, we generated chromosome‐level scaffold assemblies of these three planthopper species using HiC scaffolding technique. The scaffold N50s significantly increased to 77.63 Mb, 43.36 Mb and 29.24 Mb for N. lugens, S. furcifera and L. striatellus, respectively. To identify sex chromosomes of these three planthopper species, we carried out genome re‐sequencing of males and females and successfully determined the X and Y chromosomes for N. lugens, and X chromosome for S. furcifera and L. striatellus . The gene content of the sex chromosomes showed high diversity among these three planthoppers suggesting the rapid evolution of sex‐linked genes, and all chromosomes showed high synteny. The chromosome‐level genome assemblies of three planthoppers would provide a valuable resource for a broad range of future research in molecular ecology, and subsequently benefits development of modern pest control strategies.